On the Radius of Spatial Analyticity for the Inviscid Boussinesq Equations (Journal of Partial Differential Equations, 2020)
In this paper, we study the problem of analyticity of smooth solutions of theinviscid Boussinesq equations. If the initial datum is real-analytic, the solution remainsreal-analytic on the existence interval. By an inductive method we can obtain a lowerbound on the radius of spatial analyticity of the smooth solution.